Expression of the vitamin K-dependent proteins GAS6 and protein S and the TAM receptor tyrosine kinases in human atherosclerotic carotid plaques - Hurtado, Begoña; Muñoz, Xavier; Recarte-Pelz, Pedro; Garcia, Nadia; Luque, Anna; Krupinski, Jerzy; Sala, Núria; Frutos, Pablo García de (Thrombosis and Haemostasis, 2011)
The GAS6/ProS-TAM system is composed of two vitamin K-dependent ligands (GAS6 and protein S) and their three protein tyrosine kinase receptors TYRO3, AXL and MERTK, known as the TAM receptors. The system plays a prominent role in conditions of injury, inflammation and repair. In murine models of atherosclerotic plaque formation, mutations in its components affect atherosclerosis severity. Here we used Taqman low-density arrays and immunoblotting to study mRNA and protein expression of GAS6, ProS and the TAM receptors in human carotid arteries with different degrees of atherosclerosis. The results show a clear down-regulation of the expression of AXL in atheroma plaques with respect to normal carotids that is matched by decreased abundance of AXL in protein extracts detected by immunoblotting. A similar decrease was observed in PROS1 mRNA expression in atherosclerotic carotids compared to the normal ones, but in this case protein S (ProS) was clearly increased in protein extracts of carotid arteries with increasing grade of atherosclerosis, suggesting that ProS is carried into the plaque. MERTK was also increased in atherosclerotic carotid arteries with respect to the normal ones, suggesting that the ProS-MERTK axis is functional in advanced human atherosclerotic plaques. MERTK was expressed in macrophages, frequently in association with ProS, while ProS was abundant also in the necrotic core. Our data suggest that the ProS-MERTK ligand-receptor pair was active in advanced stages of atherosclerosis, while AXL signalling is probably down-regulated.
Keywords: PROS1; GAS6; TYRO3; AXL; MERTK; arterioesclerosis; atheroma; carotid plaque; vitamin K-dependent proteins; receptor tyrosine kinases